Cost Variation Analysis of Hypolipidemic Drugs Currently Available in Indian Pharmaceutical Market - Prajnyan Prasad Kalita; Hiteswar Saikia; Meghali Chaliha (Journal of Pharmaceutical Research)
42% of all fatalities worldwide resulting from non-communicable diseases (NCD) are attributable to cardiovascular illnesses. The availability of several brands and generic medications causes a wide range in the pricing at which they are sold. This study was conducted to raise awareness among health care workers and patients about the cost difference between different brands of the same hypolipidemic drug, so that, if possible, a cheaper effective brand can be prescribed to ensure better patient adherence. Maximum retail price (MRP) of various hypolipidemic drugs of same strength and dosage forms manufactured by different pharmaceutical companies were obtained from various online and offline sources. The maximum and minimum cost of 10 tablets/capsules were noted. The cost ratio and percentage cost variation were calculated for single drug and fixed dose combinations. The ceiling price (as per DPCO) of hypolipidemics (as per national list of essential medicines) was compared with their maximum cost. Maximum cost variation observed in case of single drug was Atorvastatin 10mg (3043.9393%), and in case of FDC was seen in Rosuvastatin 10mg + Aspirin75mg (561.341%). This study led us to the conclusion that the majority of hypolipidemic medications should be governed by DPCO in order to lessen the economic load of healthcare services on the Indian population. Keywords: Pharmacoeconomic, Cost variation, Hypolipidemic, Statins